Representasi Diskriminasi Standar Kecantikan Dalam Drama Korea True Beauty: Analisis Semiotika John Fiske - Oktaviani, Amanda; Wulandari, Yulianti Fajar; Hamid, Ali Imron (Brand Communication, 2025)
In this era, beauty has become a major issue, especially among women who are often required to meet certain standards. This phenomenon, which is often depicted in Korean dramas, can lead to discrimination against women who do not conform to the ideal image. This study aims to analyze the representation of discrimination based on beauty standards in the Korean drama True Beauty, which explicitly shows different treatment based on physical appearance. Using a descriptive qualitative method, data was collected through observation and documentation of seven scenes depicting discriminatory behavior. The analysis was conducted using John Fiske’s semiotic approach, which examines meaning at the levels of reality, representation, and ideology. The results of the study show that discrimination is represented through eight aspects of social rejection at the level of reality. At the representation level, production techniques amplify the emotional impact. At the ideology level, the drama reflects the perspective of lookism, where beauty determines an individual’s social value. This research is supported by Jon Gunnar Bernburg’s Labeling Theory, which explains how individuals labeled with social labels experience discrimination.